An exploratory study of context and factors shaping policies for integrated management of multimorbidity in Malawi - Gift Treighcy Banda-Mtaula; Elias Rejoice Maynard Phiri; Miriam Taegtmeyer; Felix Limbani; Rhona Mijumbi; Multilink Consortium (Health Research Policy and Systems)
Abstract Background Malawi faces a high burden of chronic diseases. There is an increasing prevalence of multimorbidity, where individuals experience the coexistence of two or more chronic communicable and noncommunicable diseases. International organizations such as the WHO call for policy reforms that embrace integrated disease management. Our study explored the policy environment and decisions directly relevant to the delivery of integrated multimorbidity care in Malawi. Methods This was a cross-sectional qualitative study. We used a single case-study methodology combining two sources of data: a document review of policies published between 2000 and 2023 (N = 11) and key informant interviews with policymakers (N = 13). We used the policy triangle framework to examine the context in which the policies aimed at improving management of multimorbidity were formulated, the actors involved, the policy process and the contents of the policies. Additionally, we identified barriers to the implementation of these policies. Results Malawi advocates for integrated health promotion, screening, treatment and management of chronic conditions across key policies, with a bias towards noncommunicable disease (NCD) + NCD and NCD + human immunodeficiency virus (HIV) integration. Integrated disease management was seen as a tool to accelerate achieving global and local goals such as the Sustainable Development Goals and universal health coverage. However, the formulation and implementation of these policies have been challenged by several factors including unclear burden of multimorbidity, donor-driven priorities through vertical disease funding and inadequate number and training of healthcare workers to manage multimorbidity. Conclusions We suggest that the timely provision of resources, creation of guidelines for multimorbidity management, building clinicians’ capacity and harmonization of donor–government goals should accompany policy rollout for integrated multimorbidity management.